Islamic financial system development in Kazakhstan as a way out of the crisis. - Oserbayuly Tekebayev, S. Zh. O. (Journal of Economic Research & Business Administration, 2016)
The article considers the positive sides of using advantages of Islamic finance for Kazakhstan under the crisis time. This opportunity will help developing countries as Kazakhstan, depended on commodities export, develop other sectors of real economy as production, agriculture using Islamic financial instruments. What differs Islamic finance from others is that both counterparties as a bank and a lender share profit and risks in advance, therefore both of them are interested in successful implementation of the project. It means that an Islamic bank chooses only those projects, which are expected to bring more profit and good results in future. Therefore we can say that with the help of the Islamic banks the number of enterprises will raise.